PERAN BRAND LOVE DALAM MEMBANGUN BRAND LOYALTY - Harini Abrilia Setyawati (UNIVERSITAS KARIMUN, 2023)
This study aims to analyze the effect of brand experience on brand loyalty through brand love. Data collection was carried out using a questionnaire using a Likert scale of 5 categories. This study took a sample of 50 respondents in the community in Kebumen Regency. The method used is purposive sampling. The hypothesis is tested using PLS (Partial Least Square). The results of the study show that brand experience has an effect on brand love, brand love has an effect on brand loyalty. However, brand experience has no effect on brand loyalty. The mediation test results show that brand love mediates the influence of brand experience and brand loyalty.